HUMP-SHAPED RELATION IMPLEMENTATION IN EAST JAVA - Priyo Utomo; Anton Budi Satria; Novi Sri Sandyawati; Noor Farid; Farasandya Amalia Hapsari (DIA: Jurnal Administrasi Publik, 2020)
This study aims to analyze the hump-shaped relation of regions in East Java Province. The proof of hump-shaped relation is seen from the influence of the degree of fiscal decentralization on economic growth. Fiscal decentralization analysis which is the ratio of regional original income and total regional expenditure, as well as using control variables consisting of government investment, and education which is implemented with reading and writing ability figures. The method used in this research is the econometrics approach. The model used in this study is the Fixed Effect Model with the Generalized Least Square method. The results of this study indicate that together the degree of decentralization, the degree of quadratic fiscal decentralization, government investment, the Gini ratio, the Gini squared ratio, and education significantly influence the regional economic growth in East Java Province. Partially the degree of decentralization, the degree of decentralized fiscal squared, government investment, the Gini ratio, the quadratic Gini ratio, and education also significantly affect economic growth, and show a hump-shape relationship, namely the degree of fiscal decentralization has a positive effect and quadratic fiscal decentralization hurts economic growth.